Media Smart Hafiz terhadap Kemampuan Menyimak Anak Usia Dini di RA Al-Hidayah - Fitriani Fitriani; Tuti Hayati; Momon Momon (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2026)
Early childhood listening skills in Group B at RA Al-Hidayah, Lumbung District, Ciamis Regency, remain low, characterized by a lack of focus and boredom during lessons. This study aims to assess listening skills using Smart Hafiz and soft book media and to analyze the differences in listening skills between the two. Employing a quasi-experimental approach with 20 children divided into experimental and control groups, data were collected through observation, interviews, and documentation. The results show that the average post-test score for the experimental group using Smart Hafiz reached 92 (excellent), compared to 66 (sufficient) for the control group using soft books. Hypothesis testing confirmed that the calculated t-value (4.87) exceeded the t-table value (2.101), indicating a significant difference and demonstrating that Smart Hafiz media has a substantial impact on improving children's listening skills. The findings imply that the effective use of interactive audio-visual media can create an enjoyable learning atmosphere and optimize children's information reception.